Pengaruh Labelisasi Halal Terhadap Keputusan Pembelian Konsumen Studi Kasus Pada Produk Wall’s Conello - Sujana, Sujana; Agustian, Eri (Jurnal Ilmiah Manajemen Kesatuan, 2013)
Muslims have a rule that is standard in the conduct of life. no exception to the pattern of consumption is set Islam. Syariat role in the Shari'a requires Muslims to consume everything that is lawful and forbid eating unclean things. For Muslims, taking a lawful and good (Thayib) is manivestasi of obedience and devotion to God.The purpose of this study was to determine how the influence of kosher labeling on consumer buying decisions, product case studies on the Wall's Conello STIE consumers at unity, and also see what the Muslim Students and Non-Muslim Students of kosher labeling on packaged food products. The method used in the preparation of this research is descriptive method, that is to describe or depict the state of objects in the present study is based on the facts that appear or as they are to get the conclusion of the problem and look for ways to solve through analysis conducted by the tool author Regression and correlation test. The results of the analysis of the influence of kosher labeling on consumer purchase decisions Muslims obtained the regression equation Y = 9.943 + 0.761 X, can be interpreted that, if the value is 1 then the kosher labeling purchasing decisions will be increased by 0.761, or in other words it can be concluded that the purchase decision of Wall's Conello at the moment is 9.943. With a correlation coefficient of 0.705, which means that there is a significant relationship with the closeness of the relationship between the strong and positive labeling of halal Muslim consumer purchasing decisions. As for the non-Muslim consumers obtain the regression equation Y = 1.469 + 1.003 X. With a correlation coefficient of 0.623 which means that there is a significant relationship with the closeness of the relationship between the strong and positive labeling of halal Muslim consumer purchase decisions Keywords: halal labeling, consumer purchase decision